Further gas mixtures with low environment impact. (20th September 2016) - Liberti, B.; Aielli, G.; Camarri, P.; Cardarelli, R.; Ciaccio, A. Di; Stante, L. Di; and, E. Pastori; Santonico, R.
Abstract: Further gas mixtures with low environment impact have been tested. For the best RPC performance the main effort was to look for a mixture giving a comfortable avalanche-streamer separation and a gas density ensuring sufficient primary ionization. The measurements have been carried out on small size chambers at cosmic ray rates using the waveforms recorded on the oscilloscope. Efficiencies and distributions of amplitude and charge will be presented.